Short-term Morbidities in Moderate and Late Preterm Infants - Scheuchenegger, A.; Lechner, E.; Wiesinger-Eidenberger, G.; Weissensteiner, M.; Wagner, O.; Schimetta, W.; Resch, B. (Klinische Pädiatrie, 2014)
Objective: To determine (1) the association between neonatal morbidity and gestational age and (2) the impact of pre-existing maternal medical conditions, pregnancy and birth complications on neonatal outcome in moderate and late preterm infants (32–36 completed weeks).Methods: Retrospective single-centre cohort study including all moderate and late preterm infants without congenital anomalies born at the Children’s and Maternity Hospital Linz, Austria, between January 2007 and June 2010. Stepwise regression analysis was used to determine significant associations between morbidities, maternal and perinatal complications and the gestational age.Results: Of 870 infants included the incidence of neonatal morbidities increased from 24% at 36 weeks to 43% at 35 weeks’, 55% at 34 weeks’, 75% at 33 weeks’ and 93% at 32 weeks’ gestation. Infants at 32 weeks had a 4-fold (RR: 3.88; 95% CI: 1.87–8.06) increased risk compared with those at 36 weeks, and infants of 32 weeks were 16 times (RR: 16.01; 95% CI: 9.82–26.09) more likely to be admitted to the NICU than infants of 36 weeks’. Hyperbilirubinemia (29%) and respiratory morbidity (14.3%) were the most common neonatal diagnoses. Intrauterine growth restriction, preeclampsia, preterm premature rupture of the membranes, lack of antenatal steroid administration, antepartum hemorrhage, multiple pregnancy and male gender were all associated with any kind of neonatal morbidity, admission rate to the NICU and length of hospital stay (p<0.05).Conclusion: Nearly half of all infants suffered from any morbidity, and several risk factors were identified being significantly associated with NICU admission rate and length of hospitalization.
Keywords: moderate preterm; late preterm; short-term morbidities; neonatal intensive care unit